Congenital sucrase-isomaltase deficiency. Identification of a glutamine to proline substitution that leads to a transport block of sucrase-isomaltase in a pre-Golgi compartment. - Ouwendijk, J; Moolenaar, C E; Peters, W J; Hollenberg, C P; Ginsel, L A; Fransen, J A; Naim, H Y (The Journal of Clinical Investigation, 1996)
Congenital sucrase-isomaltase deficiency is an example of a disease in which mutant phenotypes generate transport-incompetent molecules. Here, we analyze at the molecular level a phenotype of congenital sucrase-isomaltase deficiency in which sucrase-isomaltase (SI) is not transported to the brush border membrane but accumulates as a mannose-rich precursor in the endoplasmic reticulum (ER), ER-Golgi intermediate compartment, and the cis-Golgi, where it is finally degraded. A 6-kb clone containing the full-length cDNA encoding SI was isolated from the patient's intestinal tissue and from normal controls. Sequencing of the cDNA revealed a single mutation, A/C at nucleotide 3298 in the coding region of the sucrase subunit of the enzyme complex. The mutation leads to a substitution of the glutamine residue by a proline at amino acid 1098 (Q1098P). The Q1098P mutation lies in a region that is highly conserved between sucrase and isomaltase from different species and several other structurally and functionally related proteins. This is the first report that characterizes a point mutation in the SI gene that is responsible for the transport incompetence of SI and for its retention between the ER and the Golgi.